Proposta de categorização dos ex-votos do casarão : o museu vivo do Padre Cícero em Juazeiro do Norte-CE. - Brito, Carla Façanha de (2012)
The genesis of the extension ex-votos dating back to Greek and Roman people and brings in its semantic recognition of faith as embodied in the pieces that symbolize an received grace, or to be achieved, or asking for protection, being it related to healing of a disease or something else. The ex-votos can take a wide variety of forms: replicas of body parts, pictures, photos, clothing etc., deposited in churches, chapels or sacred museums. In Juazeiro do Norte-CE, the Living Museum of Father Cicero, popularly known as Big House , has a rich collection of ex-votos, becoming a space heritage, that represents the cultural and religious memory references. This study is characterized as a qualitative, descriptive, based on the content analysis, in symbolic interactionism and ethnomethodology, with the following research problems: what types of ex-votos can be found in the Living Museum of Father Cicero Juazeiro do Norte-CE? How to enforce a categorization model that enables the establish the memory of the museum's collection, which makes possible the treatment, the organization, representation, access, and retrieval of information expressed in votive offerings deposited there, taking into account the wealth and diversity of these pieces? The purpose of this study was to: analyze the discourse imaging of the Living Museum of Father Cicero of Juazeiro do Norte-CE, represented by its ex-votos, for the preparation of a model of categorization based on the Aristotelian categorization, for an indexal representation. The results of this study show that in this museum there are several categories of ex-votos that need to be arranged from the Information Science view and the use of the Aristotelian categories as a musicological terminology may bring contributions to the effective information retrieval in museum space.